Value of Preoperative Imaging and Intraoperative Histopathology in Morton's Neuroma. (September 2019) - Raouf, Tammer; Rogero, Ryan; McDonald, Elizabeth; Fuchs, Daniel; Shakked, Rachel J.; Winters, Brian S.; Daniel, Joseph N.; Pedowitz, David I.; Raikin, Steven M.
Background: Recent studies have demonstrated that clinical diagnosis of Morton's neuroma is highly correlated with operative and histopathologic diagnosis, whereas others have questioned the cost-effectiveness of intraoperative histopathology of excised specimens. The purpose of this study was to determine the utility of both preoperative imaging and intraoperative histology in the treatment of Morton's neuroma in making an accurate diagnosis, guiding treatment decisions, and altering clinical outcomes. Methods: A retrospective review was performed on all patients who underwent operative resection suspected Morton's neuroma with 4 fellowship-trained foot and ankle surgeons between 2007 and 2017. Procedures were excluded from the study if the pathology report was not available for review. Diagnoses were made either by clinical examination and/or by the results of preoperative imaging. All pathology reports were reviewed to determine the final diagnosis, considered the "gold standard." Postoperative chart notes were reviewed to determine if any treatment regimen was altered based on the pathology report revealing an alternate diagnosis other than Morton's neuroma. Two hundred eighty-seven procedures in 269 patients with 313 clinically suspected neuromas met inclusion criteria. Results: Of the 313 suspected neuromas, 309 (98.7%) were confirmed Morton's neuromas on histopathologic examination. For no patient did the results of the pathology report alter the postoperative treatment course. Preoperative imaging results were available for 179 (57.2%) suspected neuromas, with magnetic resonance imaging (MRI) and ultrasonography used to preoperatively image 121 and 71 suspected neuromas, respectively, including 13 using both. The total estimated cost of histopathologic analysis for the cohort was 143 667, and the estimated combined cost of preoperative imaging and intraoperative histopathology in our cohort totaled 278 567. Conclusion: Our study found that the diagnosis of Morton's neuroma could be made clinically with extreme accuracy and positive predictive value, calling into question the utility and costs of other imaging modalities and intraoperative sampling for histopathologic diagnosis. Level of Evidence: Level IV, retrospective case series.